Skin infections due to panton-valentine leukocidin-producing S. Aureus - Leistner, Rasmus; Hanitsch, Leif G.; Krüger, Renate; Lindner, Andreas K.; Stegemann, Miriam S.; Nurjadi, Dennis (Deutsches Ärzteblatt, 2022)
Background: Panton-Valentine leukocidin (PVL)–producing Staphylococcus aureus (PVL-SA) strains are frequently associated with large, recurring abscesses in otherwise healthy young individuals. The typical clinical presentation and the recommended diagnostic evaluation and treatment are not widely known. Methods: This review is based on pertinent publications retrieved by a selective search in PubMed, with special attention to international recommendations. Results: PVL-SA can cause leukocytolysis and dermatonecrosis through specific cell-wall pore formation. Unlike other types of pyoderma, such conditions caused by PVL-SA have no particular site of predilection. In Germany, the PVL gene can be detected in 61.3% (252/411) of skin and soft tissue infections with S. aureus. Skin and soft tissue infections with PVL-SA recur three times as frequently as those due to PVL-negative S. aureus. They are diagnosed by S. aureus culture from wound swabs and combined nasal/pharyngeal swabs, along with PCR for gene detection. The acute treatment of the skin abscesses consists of drainage, followed by antimicrobial therapy if needed. Important secondary preventive measures include topical cleansing with mupirocin nasal ointment and whole-body washing with chlorhexidine or octenidine. The limited evidence (level IIb) concerning PVL-SA is mainly derived from nonrandomized cohort studies and experimental analyses. Conclusion: PVL-SA skin infections are easily distinguished from other skin diseases with targeted history-taking and diagnostic evaluation.